1999
DOI: 10.1038/sj.onc.1202511
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 and D3 associate with the SCF complex and are coordinately elevated in breast cancer

Abstract: D-type cyclins are important cell cycle regulators that promote cellular proliferation in response to growth factors by inactivation of the retinoblastoma protein (Rb). Cyclin D1 has been shown to be overexpressed in several cancer types and to act as an oncogene in breast cancers. As D-type cyclins are rate limiting for progression into S phase, the level at which they accumulate must be carefully regulated. Several mechanisms leading to overexpression of cyclin D1 have been reported including ampli®cation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 36 publications
5
86
1
Order By: Relevance
“…We previously showed that the half-life of cyclins D1 and D3 was increased in this cell line (Russell et al, 1999). In agreement with the data obtained in primary breast cancers, the level of p21 is coordinately elevated with cyclins D1 and D3 in this cell line (Figure 3a).…”
Section: P21 Turnover Is Decreased In Mcf-7 Cellssupporting
confidence: 91%
See 4 more Smart Citations
“…We previously showed that the half-life of cyclins D1 and D3 was increased in this cell line (Russell et al, 1999). In agreement with the data obtained in primary breast cancers, the level of p21 is coordinately elevated with cyclins D1 and D3 in this cell line (Figure 3a).…”
Section: P21 Turnover Is Decreased In Mcf-7 Cellssupporting
confidence: 91%
“…We have previously shown that human cyclins D1 and D3 can both associate with a SCF complex containing the cullin Cul-1 (Russell et al, 1999). Recently, cyclin D1 has been shown to associate not only with Cul-1, con®rming our previous observation, but also with the F-box protein Skp2 (Zhong-Kang et al, 1998).…”
Section: Skp2 Associates With Cyclin D3supporting
confidence: 68%
See 3 more Smart Citations